Bond strength of orthodontic brackets with two adhesive systems - Dasmawati, Mohamad (Pusat Pengajian Sains Perubatan, 2012)
The aim of this study was to evaluate 1he bonds~ of or1hodontic brackets wi1h two adhesive systems TransbondTM XT Primer and Adhesive (CEP) and Transbond Plus Self Etching Primer (SEP) using two debonding technique between occlusal-gingival load (rod) and gingival-occlusal load (loop). Brackets were bonded to 92 extracted human premolar teeth that randomly divided into 2 groups. CEP and SEP of 46 specimens each. Before debonding, all teeth were stured in distilled water at room temperature for 24 hours. The specimens were debond using an INSTRON Universal Testing machine by two different me1hods ei1her rod or loop and the surfaces of substrate examined using Material Workstation Image Analyser (Leica DMLM) under 38x magnification. There was significantly di1rerence in mean bond strength when using two different me1hod of debonding ei1her loop or rod in the same grnup of adhesive system (p=0.04 and p=O.OS). There was alsn significant influence in ARI scores for both systems (p ~ 0.003). Application of 1he self-etching primer system in orthodontic treatment is beneficial for 1he clinician and patient in aspect of reducing time consuming for bonding procedure and removal of the remnant adhesive on the too1h surface after debonding or1hodontic brackets.